The effect of sexual education on the postpartum women's sexual self-confidence and self-efficacy: a theory-based intervention - Mana Musavi; Mitra Rahimzadeh; Monirolsadate Hosseini Tabaghdeh; Sara Esmaelzadeh Saeieh (BMC, 2024)
Abstract Introduction Pregnancy, childbirth, and the postpartum period cause significant physical and psychological changes in mothers, leading to changes in their sexual self-concept and adverse effects on their sexual self-confidence and self-efficacy. Therefore, this study aimed to determine the effect of sexual education on postpartum women's sexual self-efficacy and self-confidence. Method This randomized interventional study was conducted on 115 women who had given birth at least six weeks ago and attended healthcare centers. Using convenience sampling, the researchers randomly allocated the participants into two intervention and control groups through a block size of six. The intervention group received six 90-minute online training sessions based on the sexual self-concept model over one month, while the control group received routine care. To collect data, the self-efficacy and sexual confidence questionnaires by Buzwell and Rosenthal were used before the intervention, immediately after the intervention, and one month later. Results The study findings demonstrated no significant differences in demographic characteristics, sexual self-confidence, and sexual self-efficacy scores between the two groups before the intervention. However, the repeated measures ANOVA results revealed a substantial increase in sexual self-confidence and self-efficacy scores over time in the intervention group immediately after participating in the training sessions and one month later. Conclusion Considering the effect of training based on the sexual self-concept model on postpartum women, the researchers recommend using this model to improve their sexual self-efficacy and self-confidence after childbirth. Clinical trial registration This study is registered at the Iranian Registry Clinical Trial (IRCT20220530055025N1).